Repetitive early 68ga-fapi pet acquisition comparing 68ga-fapi-02, 68ga-fapi-46, and 68ga-fapi-74: methodologic and diagnostic implications for malignant, inflammatory/reactive, and degenerative lesions - Glatting, Frederik M.; Hoppner, Jorge; Liew, Dawn; Genabith, Antonia van; Spektor, Anna-Maria; Steinbach, Levin; Hubert, Alexander; Kratochwil, Clemens; Giesel, Frederik L.; Dendl, Katharina; Rathke, Hendrik; Kauczor, Hans-Ulrich; et al. (Journal of nuclear medicine, 2022)
68Ga-labeled fibroblast activation protein (FAP) inhibitor (68Ga-FAPI) PET targets 68Ga-FAPI-positive activated fibroblasts and is a promising imaging technique for various types of cancer and nonmalignant pathologies. However, discrimination between malignant and nonmalignant 68Ga-FAPI-positive lesions based on static PET with a single acquisition time point can be challenging. Additionally, the optimal imaging time point for 68Ga-FAPI PET has not been identified yet, and different 68Ga-FAPI tracer variants are currently used. In this retrospective analysis, we evaluate the diagnostic value of repetitive early 68Ga-FAPI PET with 68Ga-FAPI-02, 68Ga-FAPI-46, and 68Ga-FAPI-74 for malignant, inflammatory/reactive, and degenerative lesions and describe the implications for future 68Ga-FAPI imaging protocols. Methods: Whole-body PET scans of 24 cancer patients were acquired at 10, 22, 34, 46, and 58 min after the administration of 150-250 MBq of 68Ga-FAPI tracer molecules (8 patients each for 68Ga-FAPI-02, 68Ga-FAPI-46, and 68Ga-FAPI-74). Detection rates and SUVs (SUVmax and SUVmean) for healthy tissues, cancer manifestations, and nonmalignant lesions were measured, and target-to-background ratios (TBR) versus blood and fat were calculated for all acquisition time points. Results: For most healthy tissues except fat and spinal canal, biodistribution analysis showed decreasing uptake over time. We analyzed 134 malignant, inflammatory/reactive, and degenerative lesions. Detection rates were minimally reduced for the first 2 acquisition time points and remained at a constant high level from 34 to 58 min after injection. The uptake of all 3 variants was higher in malignant and inflammatory/reactive lesions than in degenerative lesions. 68Ga-FAPI-46 showed the highest uptake and TBRs in all pathologies. For all variants, TBRs versus blood constantly increased over time for all pathologies, and TBRs versus fat were constant or decreased slightly. Conclusion: 68Ga-FAPI PET/CT is a promising imaging modality for malignancies and benign lesions. Repetitive early PET acquisition added diagnostic value for the discrimination of malignant from nonmalignant 68Ga-FAPI-positive lesions. High detection rates and TBRs over time confirmed that PET acquisition earlier than 60 min after injection delivers high-contrast images. Additionally, considering clinical feasibility, acquisition at 30-40 min after injection might be a reasonable compromise. Different 68Ga-FAPI variants show significant differences in time-dependent biodistributional behavior and should be selected carefully depending on the clinical setting.
Im Titel ist die Zahl 68 hochgestellt
Gesehen am 21.11.2023